ANALISIS PEMANFAATAN ASET TETAP PEMERINTAHAN DAERAH KOTA SAMARINDA TAHUN 2019 - Evi Fariani; Siti Rohmah (OBOR: Oikonomia Borneo, 2021)
The purpose of this study is to determine whether in 2019 Mahkota II Bridge has been utilized in accordance with Government Regulation Number 34 of 2006. The analytical method used in this research is descriptive comparative using data collection techniques through interviews and surveys to determine the optimization of the use of the Mahkota II Samarinda bridge. From the results of the analysis, it is known that the use of the Mahkota II Bridge belonging to the Regional Government of Samarinda City in 2019 is not in accordance with Government Regulation Number 34 of 2006 concerning Roads, Irrigation and Networks in article 4, it is explained that the administration of public roads is obliged to ensure that it can be used as much as possible for prosperity of the people, especially increasing national economic growth by making travel costs as low as possible, this is because it has not been able to fully reduce the burden on bridge users' expenses